Applications of volatile compounds acquired from Muscodor heveae against white root rot disease in rubber trees (Hevea brasiliensis Müll. Arg.) and relevant allelopathy effects - Sakuntala Siri-udom (2018)
© 2017 British Mycological Society The bioactive compounds of the volatile metabolite-producing endophytic fungus, Muscodor heveae, were examined by the process of biofumigation for the purposes of controlling white root rot disease in rubber trees (Hevea brasiliensis Müll. Arg.). Volatile organic compounds (VOCs) of M. heveae possess antimicrobial activity against Rigidoporus microporus in vitro with 100 % growth inhibition. The synthetic volatile compounds test confirmed that the major component, 3-methylbutan-1-ol, and the minor compounds, 3-methylbutyl acetate and 2-methylpropanoic acid, inhibited root and shoot growth in the tested plants 3-methylbutan-1-ol showed ED 50 value and MIQ value on seed germination of ruzi grass, Arabidopsis thaliana Col-0 and tomato at 10, 5 and 5 μL −1 airspace, respectively. In vivo tests were carried out under greenhouse conditions using M. heveae inoculum fumigated soil that had been inoculated with R. microporus inoculum. After which, all seven treatments were compared. Significant differences were observed with a disease score at 150 d after treatment. Biofumigation by M. heveae showed great suppression of the disease. Biocontrol treatments; RMH40 (40 g kg −1 M. heveae inoculum) and RMH80 (80 g kg −1 M. heveae inoculum) were not found to be significantly different when compared with fungicide treatment (RT) and the non-infected control, but results were found to be significantly different from R. microporus infested (R) treatment. RMH40 and RMH80 revealed a low disease scores with a high survival rate of rubber tree seedling at 100 %, while R treatment showed the highest disease score of 4.8 ± 0.5 with a survival rate of rubber tree seedling at 25 %. The infected roots, appearing as a white colour. We have concluded that the bioactive VOCs of M. heveae would be an alternative method for the control of white root rot disease in rubber trees.